From waste to raw chemicals: Catalytic transformation of fusel oil by mixed metal oxides - de Lima, Livia Padilha [UNESP]; Vargas, Jorge Andrés Mora; Roveda Jr, Antonio Carlos [UNESP]; Ortega, Julieth Orduna; da Silva, Felipe Garcia [UNESP]; Cassaro, Rafael Francisco [UNESP]; Cardoso, Daniel Rodrigues; Boscolo, Mauricio [UNESP]; Metzker, Gustavo [UNESP] (Elsevier, 2024)
In this study, we detail a catalytic process for the conversion of fusel oil (FO), a by-product of ethanol production considered as waste, into valuable organic compounds, including aldehydes, alkenes, ketones, and alkylbenzenes spanning a carbon chain length from C6 to C12. The reaction was carried out in a fixed bed flow reactor at atmospheric pressure, employing mixed metal oxides (MMO) derived from hydrotalcites (HTC) as catalysts. The HTC were readily synthesized by co-precipitation method involving Mg2+ and Al3+, wherein 20 mol% Mg2+ was substituted by M2+ = Mn, Fe, Co, Ni, Cu, and Zn, and MMO obtained by HTC calcination. These catalysts offer cost-effectiveness compared to noble metal-containing ones while exhibiting remarkable activity in dehydrogenation, hydrogenation, and dehydration reactions pivotal for alcohol reactivity. The proposed methodology holds promise for large-scale industrial use and pioneers a fresh avenue for deriving value-added raw chemicals from a renewable carbon source.
Keywords: Fusel oil; Mixed metal oxides; Organic building blocks